Alkaloid and Flavonoid Phytochemical Screening on Balakka Leaves (Phyllanthus Emblica L.) - Susilawati Harahap (PT FORMOSA CENDEKIA GLOBAL, 2023)
Balakka (Phyllanthus emblica L.) contains phenolic compounds, such as geraniin, quercetin 3-β-Dglucopyranosida, kaempferol 3-β-Dglucospiranoside, isochorylagin, quercetin, and kaempferol. The purpose of this research is to identify the phytochemical content of alkaloids and types of flavonoids in balakka leaves. This type of research is qualitative with a laboratory experimental research design conducted at the Itkessu Pharmaceutical Laboratory. The results of the phytochemical screening identified positive alkaloids in the presence of a white precipitate with mayer, a brown precipitate on Wagner and an orange precipitate on Dragendroff. In positive flavonoids with a change in color to pink. Alkaloids in the pharmaceutical field are used as antitumor, antipyretic, anti-pain while flavanoids are useful as antivirals, antifungals, anti-inflammatories.